Improved dynamic balance following a lower extremity neuromuscular control program in division I women`s basketball players - Pfile, K. R.; Pietrosimone, B. G.; Gribble, P. A.; Messerth, S. M. (Journal of Athletic Training, 2012)
Context: Deficits in dynamic balance, specifically, in the anterior reach direction of the Star Excursion Balance Test (SEBT), have been used to predict acute lower extremity injury. Interventions targeting neuromuscular control have demonstrated improved dynamic balance as measured by the SEBT. However, the duration in which improved dynamic balance can be sustained following completion of an intervention remains unknown. Objective: To determine whether dynamic balance can be improved and maintained over the duration of a competitive basketball season following a 6-week neuromuscular control intervention. Design: Controlled Laboratory Study. Setting: Research Laboratory. Patients or Other Participants: Eleven Division I female basketball players (19.40 ±1.35 yrs; 178.05±7.52 cm, 72.86±10.70 kg) volunteered. Intervention(s): Participants were tested at three separate sessions: baseline; immediately following the 6-week training session (POST1) and 9 months following baseline (POST2). During each session, participants performed three trials of the anterior, posteriormedial and posteriorlateral reaches of the SEBT using each limb. The order of testing for limb and SEBT directions was randomized. The neuromuscular control and plyometric training program consisted of 18 sessions over a 6-week period, supervised and progressed by 2 Certified Athletic Trainers. The exercises focused on improving lower extremity neuromuscular control and emphasized proper landing techniques. Main Outcome Measures: The average of the 3 test trials for each leg was reported as a percentage of leg length. An average of the normalized scores for both limbs in all three directions (anterior, posteriormedial, posterior-lateral) was used for analysis. A composite score was created by averaging the normalized values from the three measured reach directions to create a single normalized value. Imputed means were calculated for two participants at one time point (one for POST1 and one for POST2) who were unable to participate due to injury. Four separate 1x3 repeated measures analysis of variance tests were performed to identify differences over time in the 4 normalized reach values (anterior, posteriormedial, posterior-lateral, composite). Post-hoc dependent ttests were performed to determine if posttests differed from pretest values. A priori significance level was set at P<0.05. Results: The mean for anterior and composite reach were significantly different over time (F2,10=5.16, P= 0.016; F2,10=6.96, P=0.005 respectively). Baseline anterior reach (63.37±3.18%) was significantly lower than POST1 (65.36±2.88%; t10=-2.71, P= 0.022) and POST2 (66.21±5.27%; t10=-2.69, P=.023). Similarly, baseline composite reach (70.41±4.08%) was lower than POST1 (73.38±419%; t10=-3.75, P= 0.011) and POST2 (74.2±4.77%; t10=-3.78, P=.004). Conclusions: Dynamic balance can be improved and sustained through a competitive athletic season following a 6-week neuromuscular control intervention. Lower extremity neuromuscular control training produces long term benefits in improved dynamic balance. Future research will need to determine if improvement in dynamic stability will be beneficial for injury risk reduction.